2012
DOI: 10.4018/irmj.2012040106
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Business Case Development Process in Inter-Organizational Enterprise System Implementations

Abstract: Creating and negotiating an inter-organizational business case (BC) for multiple-stakeholder enterprise systems is a major challenge. This paper looks closer into the factors that influence the stakeholders’ willingness to share information necessary for the BC development. The authors develop an explanatory framework showing the effect that project constellation has on the development of a shared BC. They identify several factors, such as goal consensus, cultural and semantic similarities and willingness to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Using design science [16] we developed a method (VM4IOP) that addresses some of the problems, identified in earlier research, concerning the development of a business case in inter-organizational projects [17]. Using an iterative design setup we discussed the method with several experts and academics.…”
Section: Methodsmentioning
confidence: 99%
“…Using design science [16] we developed a method (VM4IOP) that addresses some of the problems, identified in earlier research, concerning the development of a business case in inter-organizational projects [17]. Using an iterative design setup we discussed the method with several experts and academics.…”
Section: Methodsmentioning
confidence: 99%
“…But they also introduced two theories that contradict this: (1) the social impact hypothesis, that meeting the needs of various non-owner stakeholders would positively impact financial performance and (2) the available funds hypothesis (also known as the slack resources theory) that higher financial performance of firms in turn allows them to allocate more resources to environmental and social performance. For this complexity of interests (and stakeholders), Eckartz et al (2012) suggested applying co-ordination theory. It emphasises the need to understand the dependencies between different tasks and stakeholders in order to carry out a successful BC.…”
Section: Theoretical Developmentmentioning
confidence: 99%
“…So, the topic of BCs is widespread amongst several fields. Regarding the topic/field of the selected papers, only 3 focused on BCs in general Eckartz et al, 2012). Two topics/ fields were recurring most (see Table 1), namely the sustainability field, with sub-topics like corporate sustainability (9 papers), corporate social responsibility (4 papers), renewable energies (2 papers) and sustainable business (2 papers), and health related research, with subtopics like healthcare (13 papers) and occupational health (3 papers).…”
Section: Descriptivesmentioning
confidence: 99%
“…Many organizations invest in ERP under the assumption that the implemented ERP system will deal with their interrelated business goals, such as achieving their financial targets quicker, managing and streamlining their operational processes, and improving their business forecasting. For individual companies, however, the implementation of ERP systems involves great challenges, and reaping the benefits from ERP is far from straightforward (Schubert and Williams, 2011;Eckartz et al, 2012). Any successful ERP implementation requires a complete fit between the ERP system and the business processes it supports (Rotherberger and Srite, 2009;Parthasarathy and Anbazhagan, 2007;Luo and Strong, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…For the ERP implementation team to be able to make well-grounded decisions on the degree of customization for the ERP system, they need to explore and evaluate the different ERP customization choices (Rotherberger and Srite, 2009;Eckartz et al, 2012;Sarfaraz et al, 2012;Amid et al, 2012). While some approaches and frameworks (e.g.…”
Section: Introductionmentioning
confidence: 99%